1986
DOI: 10.1007/bf00015230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chloroplast DNA sequence from Chlorella ellipsoidea that promotes autonomous replication in yeast

Abstract: An EcoRI 2.7 kbp fragment from Chlorella ellipsoidea chloroplast DNA (cpDNA) cloned in YIp5 was shown to promote autonomous replication in Saccharomyces cerevisiae. The fragment was localized in the small single copy region close to the inverted repeat. The ARS activity (autonomously replicating sequences in yeast) was found to be confined within a subclone of a ca. 300 bp HindIII fragment. Sequence analysis of this fragment revealed its high AT content and the presence of several direct and inverted repeats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…3, positions 2,543-2,766) as a probe showed the presence of some related sequences to the a-elements on several other parts of cpDNA and even on the nuclear DNA from Chlorella (Yamada and Shimaji, unpublished reuslt). Recently, we revealed the presence of such a repetitive sequence with SmaI sites (like a-element) in a Chlorella cpDNA fragment that shows ARS activity (26). Schneider et al reported in the flanking regions of the chloropolast rRNA unit of Chlamydomonas reinhardii numerous tandem and iverted repeats (6).…”
Section: Open Reading Framesmentioning
confidence: 93%
“…3, positions 2,543-2,766) as a probe showed the presence of some related sequences to the a-elements on several other parts of cpDNA and even on the nuclear DNA from Chlorella (Yamada and Shimaji, unpublished reuslt). Recently, we revealed the presence of such a repetitive sequence with SmaI sites (like a-element) in a Chlorella cpDNA fragment that shows ARS activity (26). Schneider et al reported in the flanking regions of the chloropolast rRNA unit of Chlamydomonas reinhardii numerous tandem and iverted repeats (6).…”
Section: Open Reading Framesmentioning
confidence: 93%